A model of eddy current nondestructive evaluation for a current leaking crack. (October 2021) - Nakagawa, Norio
Abstract: This paper presents a model-based study of undesirable signal loss problems, often encountered by eddy current inspections of tight cracks. Possible current leakage through a portion of the crack face is the focus here as the principal mechanism of signal reduction. Two problematic types of cracking conditions are studied particularly, i.e., a surface-smeared crack and a crack under compressive stress. With a newly developed model and its numerical results, the paper shows quantitative analyses of the signal loss for the above two cases, compared to the response of a pristine surface-breaking crack in the similar geometrical configuration. Highlights: Numerical model of eddy current NDE. Modeling of closed crack inspections with a possible current leakage. Signal transition from surface-breaking to submerged cracks. Weakly singular integral formulation of crack modeling.